Treatment Of Acute Protruded Disc with Percutaneous Disc DecompressionAnd Transforaminal Epidural Steroid injection - Ammar Najim Abood Alsamarria (Diyala Journal of Medicine, 2018)
Background: The primary goal to the surgical cureof theLower-back and radicular pain is common presenting complain of herniate lumber disc and compression of the nerve root by protrusion of disc material.